(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article examines the factors of the external and internal environment that determine the effectiveness of the management system at the microeconomic level, studies the functional content of the management model of an economic entity, substantiates the directions for increasing the efficiency of management decisions.